Vaccine Development Strategies, Progresses and Challenges for Human Immunodeficiency Virus (HIV): A Review - Sisay, Tekeba; Verma, Deepak; Berhane, Nega; Tsegaw, Mesfin (The International Journal of Biotechnology, 2018)
Human immunodeficiency virus is classified under the Retroviridae family and identified as a causative agent of acquired immunodeficiency syndrome (AIDS).Since Human immunodeficiency virus (HIV) is identified as causative agent of AIDS, about 39 million people have been died and 78 million people have been infected worldwide. Despite tremendous efforts are being made to develop successful diagnosis, treatment and prevention methods, and to develop HIV vaccine the effort remains great challenge for researchers, due to extreme genetic variability of the virus. Even though vaccination of HIV is the most promising, cost effective and feasible intervention strategy to control and eradicate HIV disease route and transmission, still now we are struggling to find an elusive vaccine after thirty years and disappointing results are recorded from previous clinical trials, except the promising RV144 HIV vaccine which is phase III clinical trial with the modest vaccine efficacy. The contribution of this study is to reveal the challenges to found potent HIV vaccine during the last decades, significant lessons learnt about the basic virology, pathogenesis, immunology, HIV/AIDS treatment and HIV infection prevention and significant findings and clinical trials progresses which are currently open the way to some extent to hope that HIV vaccine development is possible.